Pengaruh Risiko Terhadap Profitabilitas di Perusahaan Minuman Beralkohol yang Tercatat di Bursa Efek Indonesia - Tiara Andani Suzuki; Veny Anindya Puspitasari (Universitas Matana, 2019)
Objective: This study aims to determine the influence of systematic risk and unsystematic risk on profitability in alcoholic beverage companies in Indonesia Stock Exchange during period 2013-2017. Design / methodology / approach: The methodology used in this study is a quantitative and descriptive approach. The population and sample in this study are the same, because alcoholic beverage companies listed on the IDX only have 2 companies. The type of data used is secondary data originating from the official website. Data analysis techniques using Multiple Linear Regression Analysis and Pool Data Regression Analysis are assisted by the application of Eviews 10 to find out the classic assumption test and hypothesis test (partial and simultaneous). Results: The results of this study indicate that interest rate risk, inflation risk, likuidity risk, credit risk, and Operational risk have an unsignificant negative effect on profitability, however exchange rate risk has a significant negative effect on profitability. Originality / value: originality in this research has no much research that use alcoholic beverages componies which produce alcoholic beverages type A during government released the rule about doesn’t allow to sell alcoholic beverages in convenience store. Keywords: Systematic Risk, Unsystematic Rick, Profitability and Pool Data